The Influence of the Zakat Fund Distribution on Poverty and Education Programs on Child Poverty in Indonesia 2015-2024 - Aida, Nasywa Hanan Putri (Center of Strategic Studies (PUSKAS) BAZNAS, 2025)
Child poverty is a complex problem in Indonesia. High levels of child poverty not only indicate economic hardship, but also signify a lack of access to adequate education. One potential solution to reduce child poverty is zakat, an Islamic social fund. This study aims to analyze the impact of zakat fund allocation for education programs in reducing child poverty in Indonesia. Utilizing data the study employs multiple regression analysis to evaluate the correlation between child poverty (the dependent variable) and zakat funds, GDP, and inflation. The results indicate that zakat distribution in the field of education has a significant negative impact on child poverty levels, meaning that an increase in zakat allocation for education can substantially reduce child poverty. Additionally, GDP also shows a significant negative effect, suggesting that overall economic improvement contributes to a reduction in child poverty. Conversely, inflation demonstrates a significant positive effect on child poverty, indicating that rising inflation exacerbates poverty by diminishing family purchasing power. These findings highlight the importance of effectively allocating zakat in efforts to combat child poverty and promote sustainable welfare.